Revitalization of UPY Foodcourt as a Communal Space for Students and the General Public - Alfian Nurfadilah, Akmal; Anggi Safitri, Ajeng; Widyasari, Herlyana; Hidayat, Nandang; Dwi Wijayanto, Affandi (Yayasan Putra Adi Dharma, 2024)
PGRI Yogyakarta University has four faculties with separate building locations totaling 3,000 students. According to the author's observation, there are several campus facilities that are not sufficient to meet the needs of students and academic civitas of UPY. One of them is the need for communal space as a support for discussing and working together tasks. The research methods used by the authors are quantitative methods of collection and analysis of secondary data, observation data, and interview data.The result of the author's analysis is an alternative design for UPY foodcourt revitalization.